2020
DOI: 10.21273/hortsci14667-19
|View full text |Cite
|
Sign up to set email alerts
|

Soil-biodegradable Mulches for Growth, Yield, and Quality of Sweet Corn in a Mediterranean-type Climate

Abstract: Plastic mulch is commonly used to produce many vegetable crops because of its potential to decrease days to harvest, control weeds, and improve soil moisture conservation. However, use of plastic mulch is relatively new for sweet corn (Zea mays L.) in North America. We compared five plastic soil-biodegradable mulches [BDMs; Bio360, Organix AG, Clear Organix AG, Naturecycle, and Experimental polylactic acid/polyhydroxyalkanoates (Metabolix, Inc., Cambridge, MA)] and a paper mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 25 publications
7
30
0
Order By: Relevance
“…Such differences might be attributed to the higher plant uptake rate with higher yield under mulching. It has been found that sweet corn yields under mulch were 40-50% higher than those recorded in plots without mulch (2017 and 2018) [71]. It might also be because the mulch film prevents rainfall infiltration, thus mitigating and even preventing runoff and soil erosion.…”
Section: Film Mulching Effects On Nutrients In the Soilmentioning
confidence: 96%
“…Such differences might be attributed to the higher plant uptake rate with higher yield under mulching. It has been found that sweet corn yields under mulch were 40-50% higher than those recorded in plots without mulch (2017 and 2018) [71]. It might also be because the mulch film prevents rainfall infiltration, thus mitigating and even preventing runoff and soil erosion.…”
Section: Film Mulching Effects On Nutrients In the Soilmentioning
confidence: 96%
“…5B). Concurrent with the stored mulch field trials described herein, we performed a larger field trial at both locations that employed new mulch rolls, which were obtained in 2017 (Ghimire et al, 2020;Moore and Wszelaki, 2019). The PSE ratings for BioAgri in the new mulch field studies (40% to 60% and 6% to 8% for Knoxville and Mount Vernon, respectively) were slightly lower than those observed in the stored mulch field trials (Ghimire et al, 2020;Moore and Wszelaki, 2019).…”
Section: Changes Of Chemical Properties Of Mulches During 3 Years Of Storagementioning
confidence: 99%
“…Concurrent with the stored mulch field trials described herein, we performed a larger field trial at both locations that employed new mulch rolls, which were obtained in 2017 (Ghimire et al, 2020;Moore and Wszelaki, 2019). The PSE ratings for BioAgri in the new mulch field studies (40% to 60% and 6% to 8% for Knoxville and Mount Vernon, respectively) were slightly lower than those observed in the stored mulch field trials (Ghimire et al, 2020;Moore and Wszelaki, 2019). It is noted that the test crops employed for the field studies differed between stored and new mulch trials in Mount Vernon (pie pumpkin and sweet corn, respectively) and between locations, although both the stored and new mulch trials employed bell peppers as the cropping system in Knoxville.…”
Section: Changes Of Chemical Properties Of Mulches During 3 Years Of Storagementioning
confidence: 99%
“…The quest to find a suitable degradable material for mulching films has been widely discussed in the research field [ 170 , 171 , 172 ]. RC has been prominently studied for its unique properties, such as biodegradability and remarkable mechanical and thermal properties [ 173 , 174 ].…”
Section: The Potential Applications Of Regenerated Cellulose Products For Agriculturementioning
confidence: 99%